Products and technologies for treating patients with evidence-based pressure ulcers - Tatiana Neves Figueira; Marli Terezinha Stein Backes; Neide da Silva Knihs; Isabel Cristina Alves Maliska; Lúcia Nazareth Amante; Maria Lígia dos Reis Bellaguarda (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to identify products/technologies for treating patients with pressure ulcers with an evidence level 1. Method: this is an integrative literature review. A survey of studies was carried out using the United States National Library of Medicine Portal, Scientific Electronic Library Online, Virtual Health Library, National Library of Medicine(®), The Cumulative Index to Nursing and Allied Health Literature, Latin American and Caribbean in Health Sciences, Nursing Database. Results: sixteen articles were selected with level of evidence 1. The findings were categorized into five categories: Topical therapy to promote healing; Alternative therapy to promote healing; Topical therapy to promote debridement; Topical therapy to minimize lesion contamination; Topical therapy to reduce lesion size. Final considerations: the 17 products/technologies identified favor/fast healing, debridement, minimize contamination and reduce lesion size to accelerate healing.